THE EFFECT OF COMPENSATION, WELFARE BENEFITS, EDUCATION AND TRAINING TO WORK PRODUCTIVITY IN PT. MULTI SERVISINDO SARANA SUBSTATION SEMARANG (PENGARUH KOMPENSASI, TUNJANGAN KESEJAHTERAAN, PENDIDIKAN DAN PELATIHAN PADA PT. MULTI SERVISINDO SARANA CABANG SEMARANG) - Ahmad Latif Rahardianto; Azis Fathoni; Leonardo Budi Hasiholan (Jurnal Ekonomi dan Bisnis Kontemporer, 2016)
This research purposes to finding the effect of the influence between compensation, awelfare allowance, education and training employees on the increase in labor productivityemployees on PT. Multi Servisindo Sarana Cabang Semarang, on increased laborproductivity employees. So as to from the results of research is expected can provide anillustration of the influence of compensation, allowance, education and training on increasedlabor productivity employees.The testing of hypotheses in this research used a multiple linear regression analysis, testt ,test f and coefficients determination (R2 ). Population in this research is 100 an employee ofPT. Multi Servisindo Sarana Cabang Semarang, carrying using a technique clusters ofsampling, while the sample is 80 employees who were chosen with a random (scrambled).Based on the results of his research on the influence compensation, allowance,education, and training to work productivity an employee at PT. Multi Servisindo SaranaCabang Semarang, obtained the result that the influence of all variable independentemployees of productivity showed the significant, it can be argued that all variable significantpositive on productivity employees.Keywords: compensation, allowance, education, training, productivity employees.